Comparative Micrometrical studies on the Trachea of Pashmina, Bakerwali and Non-Descript Goats of Jammu and Kashmir State - Nabi, Neelofar (Indian Journal of Veterinary Anatomy, 2020)
The present study was undertaken to describe and compare the micrometrical features of the trachea of adult Pashmina, Bakerwali and non-descript goats (ten each). The mean values for the height of tracheal epithelium were recorded as 98.65±1.33μm, 92.45±1.84μm and 84.55±2.0μm for Pashmina, Bakerwali and nondescript goats, respectively. The tracheal mucosal thickness was found to be significantly (P>0.05) high in Pashmina goat. It was also observed that the mean value in regard to the population of Clara cells in trachea was the highest in Pashmina (10.64±0.17), followed by Bakerwali (8.6±0.16) and non-descript (7.14±0.20) goats, respectively.